Strategi Inovatif dalam Pembelajaran IPS di Sekolah Dasar - Ahmad Ahmad (Jurnal Kajian Pendidikan dan Cakrawala Pembelajaran, 2025)
Social Studies (IPS) education in elementary schools plays a vital role in shaping students’ social awareness and critical thinking skills. However, traditional teaching methods often fail to engage students, leading to low interest in the subject. This study reviews innovative strategies in IPS learning, including project-based learning, technology integration, and interactive media.The findings indicate that project-based learning enhances students’ understanding by linking concepts to real-world applications. The use of technology, such as digital media and simulations, makes learning more engaging, while interactive media like animations and digital books cater to different learning styles. These strategies not only improve comprehension but also foster active participation and motivation among students. Implementing innovative approaches in IPS education can significantly enhance learning outcomes. Further research is needed to assess the long-term impact of these strategies in different educational settings.